Oxygen uptake, blood and lactate concentration during cross-country skiing at race speed - Evertsen, F.; Welde, B. (Book of Abstracts. 5th International Congress on Science and Skiing, Dec. 14 - 19, 2010, St. Christoph am Arlberg, 2010)
INTRODUCTION: While previous investigations indicates that cross-country (x-c) skiers repeatedly perform well above peak aerobic power, even during longer races (for ref., see Saltin, 1997), we have shown that high-level female Juniors are unable to ski at intensities close to their VO2max or maintain an average intensity above that corresponding to their onset of blood lactate accumulation (OBLA, 4 mmol L-1) even during races lasting less than 25 min (Weide et al., 2003). However, this has not been examined in elite x-c skiers and, thus, the aim of this study was to measure VO2 and blood and muscle lactate concentration during x-c skiing at competition speed in male elite skiers and to compare these entities to the subjects' VO2max and the VO2 corresponding to the OBLA during skiing.